As vertentes características e os sistemas pedológicos como instrumentos de análise para a identificação das fragilidades e potencialidades ambientais na Bacia Hidrográfica do Paraná 3 - Rocha, Anderson Sandro da (2016)
The present work has the objective of identifying and detailed analysis of the characteristic slopes and the pedological systems associated to the different landscape units of the Paraná watershed 3, in order to understand their fragilities and environmental potentialities. Using the theoretical and methodological precepts of the structural analysis of the pedological cover, the evaluation of the hypsometric integral indices and the concepts of integrated analysis of the landscape, it was possible to understand the morphopedological behavior and the geomorphological evolution of the three large topographic sectors of the watershed: sector of plateau, which contemplates the Cascavel unit; the intermediary, where the unity of San Francisco is located; and the demoted sector, represented by the Foz do Iguaçu unit. In the upper sector, the typical slopes are characterized by convex-rectilinear morphologies and dominant pedological systems consisting of Red Latosol - Regolithic Neosol - Red Latosol and Red Latosol - Red Nitosol. In the middle sector, the convex-concave-rectilinear slopes predominate, segmented in levels, with a pedological system formed by the Regolithic Neosol - Red Nitosol - Neosol Litholic. In the low sector, on the margins of the Paraná River, dominate the rectilinear slopes and the pedological system typically composed of the Red Latosol - Red Nitosol. The correlation of the morphopedological allowed us to understand that the three sectors are in differentiated stages of geomorphological evolution. The upper compartment was less affected by the erosion processes, with less intense denudation of the relief, while the lower compartment had a higher performance of erosion processes and greater denudation. Thus, data from hypsometric integrals have shown that regional geomorphological evolution has been occurring through the advance of remanent erosion processes, which is currently more intense in the intermediate compartment. The knowledge of the interactions between the geomorphopedological domains and the elements of the geoecological structure allowed us to understand the fragilities potential and emergent, with the spatialisation of the areas of stability / environmental instability of the watershed. In general terms, the correlation of spatial and numerical data made it possible to evaluate that the potential fragility presented a predominance of the weak (45.21%) and very weak (30.41%) classes, while the emergent fragility showed greater expressiveness of the Fragility (41.40%), followed by the weak fragility class (34.30%). In this context, it was also possible to evidence different conditions of land use capacity. The determination of the capacity classes and subclasses, with their respective environmental restrictions, allowed us to understand that the morphology of the slopes and the distribution of the pedological cover present preponderant information to indicate appropriate soil conservation practices in the territorial scope of the Paraná watershed 3.